Deep Breathing Increases Heart Rate Variability in Patients With Rheumatoid Arthritis and Systemic Lupus Erythematosus. Issue 7 (19th October 2021) - Rovsing, Cecilie; Rovsing, Helene; Liboriussen, Caroline Hundborg; Jensen, Mette Kjeldsgaard; Andersen, Sally Søgaard; Andersen, Stine Søgaard; Kristensen, Salome; Jochumsen, Mads
Abstract : Background/Objective: Autoimmune diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) have been associated with an impaired function of the autonomic nervous system and reduced vagus nerve (VN) tone measured through lower heart rate variability (HRV). Targeting the VN through electrical stimulation has been proposed as a treatment strategy with promising results in patients with RA. Moreover, it has been suggested that the VN can be stimulated physiologically through deep breathing. In this study, the aim was to investigate if the VN can be stimulated through deep breathing in patients with RA and SLE, as measured by HRV. Methods: Fifty-seven patients with RA and SLE performed deep breathing exercises for 30 minutes in this explorative study. Before the breathing exercise, 2 electrocardiogram recordings were obtained to determine the patient's baseline HRV during rest. After the 30-minute breathing exercise, 5 minutes of electrocardiogram recordings were obtained to determine postintervention HRV and used as a measure of vagal activity. Results: No change was observed in the HRV between the 2 recordings prior the exercise, but the heart rate and HRV significantly decreased and increased, respectively, after the deep breathing exercise. Conclusions: HRV can be modulated in patients with RA and SLE; this may have implications for future treatment with medications in conjunction with deep breathing. However, the biological and clinical effect of deep breathing must be investigated in future studies.